The impact of Corporate Social Responsibility on employee’s engagement: Exploratory study of IT companies in Morocco. - CHAKRA, Raja; HATHOUT, Sara; CHAREF, Fatima (Revue Internationale des Sciences de Gestion, 2021)
Research in management science has offered a body of work focused on the theme of corporate social responsibility (CSR) and that of organizational behavior. However, research seems limited on the interaction of these two variables. The concept of CSR appears relevant because it questions organizational functioning and the role of human resources management (HRM). We opted for the case of Information Technology (IT) companies in Morocco as a field of investigation. Our research focuses on the question: Can employee’s perception of CSR have an effect on their attitudes and behaviors as organizational commitment? This article highlights the effect associations that tie our two variables through the analysis of nineteen qualitative interviews. The results enrich the understanding of the impact of the perception of CSR on the behaviors and attitudes of employees in terms of organizational commitment. The exploratory nature of our research leads us to choose a qualitative methodology with a comprehensive aim. Semi-structured interviews with 19 individual made it possible to explore the different perceptions of employees and the resulting organizational commitment behaviors.